Protecting against summation of pain - Mauceri, Daniela; Kuner, Rohini (Neuron, 2022)
Temporal summation in the spinal cord is linked to pathological pain. In a translational genetic association study in this issue of Neuron, Trendafilova et al. (2022) identify the sodium-calcium exchanger 3 as a negative regulator of temporal summation and hypersensitivity via its modulation of calcium homeostasis.
Gesehen am 28.02.2023
Available online 17 August 2022, Version of Record 17 August 2022